The Effect Of Perceived Usefulness and Perceived Convenience on Customer Decision in Using BSI Mobile - Shalihah, Bunga Mar'atush; Lidia Desiana; Fernando Africano (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2024)
Customer decisions are very important for a bank, meaning that a bank must maintain a good reputation in order to create a positive perception for society and customers. Mobile banking is one of the services provided by banking companies to make it easier for customers to make transactions. In using mobile banking, of course it is based on the customer's perception of a service, therefore there are several things that are measured in determining the customer decision, namely perceived usefulness and perceived convenience. This study aims to determine the effect of perceived usefulness and perceived convenience on customer decisions in using BSI Mobile. Collection of customer questionnaires measured using a Likert scale is a data collection method in this study. The population of customers who use BSI Mobile in this study is 6,701 people with the characteristics of active customers who use BSI Mobile in their daily transactions, and the number of samples in this study is 100 people who are determined from the sampling technique, namely purposive sampling. The results obtained using the t test (partial) show that perceived usefulness and perceived convenience have a positive and significant effect on customer decisions in using BSI Mobile.